Cost of Quality Analysis on Tailors’ Industry in Aceh - Dinaroe Dinaroe; Syarifah Umaira; Fazli Syam BZ (Universitas Syiah Kuala, 2018)
Objective – This research aims to explore and find out the application of Cost of Quality in Managerial Accounting perspective on the Tailor’s businesses in Banda Aceh during the period of 2015 – 2017. In addition, the research purposes are to analyze the firms plan and control of the Cost of Quality and how the firms arrange the cost in order to improve the quality with minimum budget cost.Design/methodology – The study uses qualitative descriptive research approach and being conducted using data from the firms annual reports and additional in-depth interview with the owners. The technique of purposive sampling is used in this study with the data availability criteria. The population of the research are the Micro, Small and Medium Enterprises (MSMEs) in Banda Aceh, and the sample criteria among others are tailor industry factories in Banda Aceh that have already prepared financial report during the observed period. CV Kuta Alam Tailor and CV Aceh Moda Tailor have been selected as the samples and as the study case location. The researcher analyzed the data by analyzing and examining the costs incurred by the firms, at how much and what kind of it, related to the cost of quality and cost of goods sold before and after the cost of quality is being added. Results – The result shows that CV. Kuta Alam Tailor and CV. Aceh Moda Tailor in term of cost of quality is still above 2.5% of the sales, thus indicates that the cost extravagancy and there are big differences in the cost of the goods sold if the cost of quality is included into the cost of goods sold. In addition, it is also found that both firms do not make a quality cost report specifically.Research limitations/implications – The research is based on the qualitative approach and does not using empirical research tools, so then it can not be generalized for overall tailor industry in Aceh nor Indonesia, outside of the observed firms and location. Therefore, it is necessary for the future research to explore more this phenomenon by using quantitative approach in order to analyze the influence of quality cost and firm performance or budget efficiencies.Novelty/Originality – The research focuses on analyzing and examining the cost of Quality in manufactur industry, particularly in the Job-Process Industry, such as Tailor industry is still very novice and need to be nurtured. Thus, this study contributes to this area by examining the implementation and aplication of the cost of quality whether the cost information can produce managerial information through financial and managerial reporting that will improve the product quality toward cost effeciency.Keywords Cost of Quality, Prevention Cost, Appraisal Cost.